Problems and trends of higher education system in the information society: social and philosophical analysis - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the main problems and tendencies of development of higher education in the early 21st century.